Classifying fifty-seven Cucumis (Cucurbitaceae) accessions into six species using leaf architectural traits (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Masungsong LA, Alcala AA, Buot IE Jr., Belarmino MM. 2022. Classifying fifty-seven Cucumis (Cucurbitaceae) accessions into six species using leaf architectural traits. Biodiversitas 23: 4006-4017. In gene banks, there are myriads of accessions that need to be studied, grouped, classified and organized to the proper taxon and hence, be able to manage the accessions efficiently. Using leaf architecture traits, it is the objective of this study to determine the identity and classify the 57 Cucumis accessions in the genebank of Hortanova Farm and Research Center, East-West Seed Company, Inc., Lipa City, Batangas, Philippines.  Five hundred thirteen Cucumis leaf samples across the 57 accessions were collected, measured, thoroughly investigated, and described using leaf architectural characters. Results of leaf architectural analyses focusing on the blade class, apex angle, secondary vein spacing, tertiary vein angle in relation to primary vein, and areole development, revealed that the 57 accessions can be grouped into six (6) species of Cucumis, namely, C. melo subsp. agrestis (Naudin) Pangalo, C. melo var. texanus Naudin, C. melo var. flexuosus (L.) Naudin, C. zambianus Widrl, J.H.Kirkbr., Ghebret. & K.R.Reitsma, C. sativus L., and C. sativus var. hardwickii (Royle) Gabaev. Cucumis sativus and C. sativus var hardwickii were delineated from the rest of the species for having a macrophyll blade class, an odd lobed acute apex angle and an obtuse tertiary vein angle in relation to the primary vein. This delineation is illustrated in the constructed dichotomous botanical key. Utilizing leaf architecture characters is an effective technique to characterize, identify and classify closely related taxa possessing confusing characters.
Keywords: areole development, blade class, marginal ultimate venation, taxonomic tool, venation patterns